Integration of Cultural Sustainabılıty in Rural Traditional Aghirda (Ağırdağ) Houses - Eken, Cemaliye (Eastern Mediterranean University (EMU), 2012)
[Abstract Not Available]
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2012. Supervisor: Assoc. Prof. Dr. Özgür Dinçyürek.
Keywords: Architecture; Traditional Houses - Agirdag (Cyprus, North); Vernacular Architecture - Agirdag (Cyprus, North); Architecture, Domestic - Cyprus, North